Phase‐Locked Loop Using Complex‐Coefficient Filters for Grid‐Connected Inverter. Issue 4 (December 2014) - Ohori, Akihiro; Hattori, Nobuyuki; Funaki, Tsuyoshi
SUMMARY Recently, photovoltaic (PV) power systems have attracted considerable attention in attempts to mitigate global warming. In a PV power system, it is necessary to synchronize the grid voltage when a PV inverter is interconnected with a grid. This paper proposes a high‐speed and high‐precision phase‐locked loop (PLL) using complex‐coefficient filters for a single‐phase grid‐connected inverter. The proposed PLL can detect the phase of grid voltage that has superimposed harmonic components for grid fault. Moreover, numerical results show the effectiveness of the proposed method.